Green Growth, Corporate Social Responsibility, and Bank Profitability: Synergies for Sustainable Finance in the Middle East and North Africa Region - Nouaili, Makram; Khemiri, Mohamed Ali (International Journal of Economics and Financial Issues, 2025)
The main purpose of this paper is to investigate the relationship between Green Growth (GGI), corporate social responsibility (CSR) and bank profitability measured by return on assets (ROA) and return on equity (ROE) in the Middle East and North Africa (MENA) region. It uses a sample of 40 MENA banks during the period 2010-2022 and performs the System Generalized Method of Moments (SGMM). Empirical findings of the analysis reveal that bank profitability is positively associated with the Green Growth index (GGI) only for the (ROE). We found that CSR practices increases the profitability of banks in the Middle East and North Africa. Furthermore, findings support evidence that banks adopting green growth strategies through CSR initiatives experience enhanced profitability. The results of this paper could have important policy implications for both policymakers and bankers in the MENA region.